IMPLEMENTASI MAKNA SAKRAMEN EKARISTI DALAM KELUARGA KATOLIK - Sembiring, Mimpin; Sinulingga, Aldi Alfrianza (IN VERITATE LUX, 2018)
The Eucharist as the source and pinnacle of the liturgy involves all people participating in Christ's sacrifice. It is hoped that the participation of all people in the Sacrament of the Eucharist will enable people to appreciate the meaning of unity, the meaning of sacrifice, and the meaning of preaching in the sacrament of the Eucharist. Understanding the meaning of the Eucharist directs people to realize it in the Catholic family. This is because all activities carried out in family life flow from the Eucharist and always draw strength from the Eucharist. However, the application of the meaning of the Sacrament of the Eucharist in Catholic families has begun to become less visible within the family. This research uses qualitative research methods using observation, interview and documentation analysis techniques. Observations are carried out by observing events and behavior that are needed to support the research being carried out. The interview technique is carried out by asking questions to the informant, to obtain the information needed according to the research. Also documentation as supporting evidence for research results. The research results show that the implementation of the meaning of the unity of the sacrament of the Eucharist in the Catholic family is carried out through joint prayer, personal prayer, eating together, gathering with the family, and the unity of husband and wife participating in church activities.